SPATIO-TEMPORAL ANALYSIS OF LAND COVER CHANGE (1990–2021) AND ITS IMPLICATIONS ON HYDROLOGICAL RISK IN THE CENTRAL CILIWUNG WATERSHED (DEPOK–SOUTH JAKARTA) : Dinamika Perubahan Tata Guna Lahan di DAS Ciliwung Bagian Tengah dan Implikasinya terhadap Lingkungan Perkotaan - Yan Oktaria, Belicka; Tri Juniati, Atie; Teguh Prasidha, I Nyoman (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
The Central Ciliwung Watershed represents a strategic hydrological transition zone between upstream and downstream Jakarta that has experienced rapid urban transformation over the past three decades. This study analyzes spatio-temporal land cover change from 1990 to 2021 and evaluates its implications for hydrological risk. Multi-temporal Landsat Collection 2 Level-2 imagery (30 m spatial resolution) for 1990, 2000, and 2011 and Sentinel-2 Level-2A imagery (10 m spatial resolution) for 2021 were processed. Sentinel-2 imagery was resampled to 30 m to ensure spatial consistency. Atmospheric correction and cloud masking were applied using QA bands and Scene Classification Layer (SCL). Supervised classification with the Random Forest algorithm produced an overall accuracy of 87.6% and a Kappa coefficient of 0.84. Built-up land expanded from 8,240.24 ha (23.9%) in 1990 to 29,258.90 ha (86.3%) in 2021, while agricultural and vegetated areas declined substantially. Increasing impervious surfaces reduce infiltration capacity and elevate runoff coefficients, potentially intensifying peak discharge. These findings highlight the importance of integrated watershed-scale planning and infiltration-based urban drainage strategies.